An Analysis of Flouting Maxim in Utterances of Main Characters in Elemental: Forces of Nature Movie - Nur Imani, Sofia Ayu; Pradipta, Bramantya (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research aims to determine the flouting of the maxims used in the main character of Elemental: Forces of Nature movie through qualitative methods using Herbert Paul Grice's theory of cooperative principles. To conduct this study, the researcher collected data by observing the utterances produced by the characters Amber Lumen and Wade Ripple in the Elemental: Forces of Nature movie, which was downloaded from the Disney+ Hotstar application. The purpose of this research is to determine the types of flouting maxims. Then, identify and analyze flouting maxims often used in the main character's utterances. The findings show that the main character flouts the maxim forty times in this movie. It is known that the maxim of quantity appears fourteen times, the maxim of quality appears four times, the maxim of relevance appears nineteen times, and the maxim of manner appears three times. This means that the maxim of relevance is the maxim most often flouted by the main character, while the least flouted maxim is the maxim of manner. Wade Ripple frequently flouts the maxim of relevance ten times, and Amber Lumen only nine times. Lastly, Amber Lumen often flouts the maxim of manner three times. Keywords: Cooperative Principle, Elemental: Forces of Nature, Flouting Maxim, Herbert Paul Grice’s Theory.